A Phenomenological and Grounded Theory Study of Women’s Experiences in Drug Court: informing Practice Through a Gendered Lens - Gallagher, John Robert (Women & criminal justice, 2017)
Drug courts have been a growing part of the criminal justice system since 1989. This qualitative study adds to the existing literature by developing an in-depth understanding of drug court from a woman’s (N = 25) perspective. Phenomenology and grounded theory guided the data collection and analysis, resulting in three themes. First, the women found the drug court team to be compassionate and empathetic, which they reported supported them in being successful in the program. Second, the majority of women reported histories of trauma and felt that the drug court could be improved by offering them more resources to treat their trauma. Third, the majority of women reported being single mothers and they shared examples of how being a single parent was a challenge to being successful in the drug court. Implications for drug court practice are discussed.